A comparative study of various existing malware analysis methods. (22nd August 2019) - Dahiya, Namita; Mahajan, Shilpa
With the advancement of technology, today's world is a digital world where digital technology is generating new world of possibilities and opportunities and we are abandoned with digital data over the network that needs to be exchanged with many organisations, devices and users. This data needs to be a secure data and malware is one type of threat to this data. There are many forms of malware that can damage this sensitive data. This paper includes various malware detection techniques to detect various known and unknown binaries and presents a detailed analysis of current methods of malware detection and a malware analyser tools.